HUBUNGAN ANTARA PENGETAHUAN PENDERITA TUBERKULOSIS TENTANG PENCEGAHAN PENULARAN TUBERKULOSIS DENGAN PERILAKU PENCEGAHAN PENULARAN TUBERKULOSIS DI PUSKESMAS ATAPUPU KABUPATEN BELU - Maria Jita Iba Badu; Tedy Candra Lesmana; Siti Aspuah (STIKES Wira Husada Yogyakarta, 2015)
ABSTRACT Background: Knowledge of TB patients can influence the behavior of TB patients in order to prevent the transmission of TB. TB patient knowledge about prevention of TB transmission that will improve the behavior of TB patients to prevent the transmission of TB. In the preliminary study found 8 patients with TB from 10 TB patients whose knowledge is less supportive behavior prevention of TB transmission in health centers Atapupu Belu. Thus researchers want to learn about the relationship of TB patient knowledge about prevention of transmission of TB to prevent the transmission of TB in behavioral health center Atapupu.Objective: To determine the relationship between knowledge about the prevention of transmission of TB patients with TB prevention of TB transmission in behavioral health center Atapupu Belu.Methods: The study was a quantitative noneksperimen using analytic observational with cross sectional approach. Results: Spearman rank correlation analysis, knowledge about TB prevention of TB transmission in the health center are less well categorized Atapupu of 46.7%, and the behavior of TB patients are less well categorized by 53% the number of those 30 patients. Conclusion: There is a relationship between knowledge about the prevention of transmission of TB patients with TB prevention of TB transmission in behavioral health center Atapupu Belu.